2005
DOI: 10.1210/jc.2004-2257
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Factor 3 Serum Levels in 135 Normal Men and 85 Men with Testicular Disorders: Relationship to the Luteinizing Hormone-Testosterone Axis

Abstract: Insulin-like factor 3 (INSL3) serum levels were measured in 135 andrologically well-characterized normal men and 85 patients with testicular disorders to investigate how the hormone, which is a major secretory product of human Leydig cells, is related to testosterone (T), LH, and semen quality. INSL3 was measured by using a newly developed fluorescence immunoassay. Median (2.5-97.5 percentiles) INSL3 serum levels were as follows: normal men (n = 135), 0.99 (0.55-1.73) ng/ml; infertile men (n = 23), 1.11 (0.60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
177
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(203 citation statements)
references
References 29 publications
18
177
1
7
Order By: Relevance
“…In fact, with the establishment of a functional hypothalamic-pituitarygonadal (HPG) axis during puberty, boar Leydig cells appear to be most responsive to LH at puberty as characterized by a dramatic increase in cell number, cell volume, LH receptor number, and intracellular organelles of the Leydig cells (Peyrat et al 1981, Lunstra et al 1986, Franca et al 2000, and also as indicated by our findings that the testosterone levels increased progressively toward puberty with an irregular fluctuation at subsequent ages, whereas E 2 levels increased in a stepwise fashion with advancing age, consistent with previous reports (FlorCruz & Lapwood 1978, Allrich et al 1982, Schwarzenberger et al 1993, Estienne et al 2000. In addition, in other species, INSL3 has been reported to be constitutively expressed and secreted by the Leydig cells under the long-term effects of LH/hCG and is not acutely regulated by LH/hCG and other hormones influencing Leydig cell differentiation, such as insulin-like growth factor1 (IGH1) (Foresta et al 2004, Bay et al 2005, Sadeghian et al 2005. In line with the lack of an acute stimulatory effect of LH, we did not find any correlation between LH and INSL3 in boars, although there are conflicting findings showing a positive correlation between them in normal men (Foresta et al 2004, Ferlin et al 2006.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, with the establishment of a functional hypothalamic-pituitarygonadal (HPG) axis during puberty, boar Leydig cells appear to be most responsive to LH at puberty as characterized by a dramatic increase in cell number, cell volume, LH receptor number, and intracellular organelles of the Leydig cells (Peyrat et al 1981, Lunstra et al 1986, Franca et al 2000, and also as indicated by our findings that the testosterone levels increased progressively toward puberty with an irregular fluctuation at subsequent ages, whereas E 2 levels increased in a stepwise fashion with advancing age, consistent with previous reports (FlorCruz & Lapwood 1978, Allrich et al 1982, Schwarzenberger et al 1993, Estienne et al 2000. In addition, in other species, INSL3 has been reported to be constitutively expressed and secreted by the Leydig cells under the long-term effects of LH/hCG and is not acutely regulated by LH/hCG and other hormones influencing Leydig cell differentiation, such as insulin-like growth factor1 (IGH1) (Foresta et al 2004, Bay et al 2005, Sadeghian et al 2005. In line with the lack of an acute stimulatory effect of LH, we did not find any correlation between LH and INSL3 in boars, although there are conflicting findings showing a positive correlation between them in normal men (Foresta et al 2004, Ferlin et al 2006.…”
Section: Discussionsupporting
confidence: 89%
“…The serum concentration of testosterone is most often in the lower half of the reference range of healthy males, and rarely below the reference range. Inhibin B is below the detection limit in the vast majority of KS adults reflecting the absent spermatogenesis (39), whereas the circulating concentrations of AMH and INSL3 are significantly reduced compared with healthy males (40,45,46). Mean testes volume in KS adults is 3.0 ml (range 1.0-7.0) as compared with 22 ml in healthy adult males (Fig.…”
Section: Testicular Endocrinologymentioning
confidence: 92%
“…INSL3 is a circulating peptide that can be measured by standard immunoassay (26). Levels are increased at puberty and adulthood while they are undetectable in females.…”
Section: Transabdominal Phasementioning
confidence: 99%